Combined approaches for increasing fetal hemoglobin (HbF) and de novo production of adult hemoglobin (HbA) in erythroid cells from β-thalassemia patients: treatment with HbF inducers and CRISPR-Cas9 based genome editing - Finotti, Alessia; Gambari, Roberto (Frontiers in Genome Editing, 2023)
Genome editing (GE) is one of the most efficient and useful molecular approaches to correct the effects of gene mutations in hereditary monogenetic diseases, including β-thalassemia.CRISPR-Cas9 gene editing has been proposed for effective correction of the β-thalassemia mutation, obtaining high-level "de novo" production of adult hemoglobin (HbA). In addition to the correction of the primary gene mutations causing β-thalassemia, several reports demonstrate that gene editing can be employed to increase fetal hemoglobin (HbF), obtaining important clinical benefits in treated β-thalassemia patients. This important objective can be achieved through CRISPR-Cas9 disruption of genes encoding a transcriptional repressor of g-globin gene expression (such as BCL11A, SOX6, KLF-1) or their binding sites in the HBG promoter, mimicking non-deletional and deletional HPFH mutations. These two approaches (β-globin gene correction and genome editing of the genes encoding repressors of γ-globin gene transcription) can be, at least in theory combined.However, since multiplex CRISPR-Cas9 gene editing is associated with documented evidence concerning possible genotoxicity, this review is focused on the possibility to combine pharmacologicallymediated HbF induction protocols with the "de novo" production of HbA using CRISPR-Cas9 gene editing.